Prevalence of Variant GTRIStaphylococcus aureus Isolated from Dairy Cow Milk Samples in the Alpine Grazing System of the Aosta Valley and Its Association with AMR and Virulence Profiles - Valentina Monistero; Delower Hossain; Sara Fusar Poli; Elizabeth Sampaio de Medeiros; Paola Cremonesi; Bianca Castiglioni; Filippo Biscarini; Hans Ulrich Graber; Giulia Mochettaz; Sandra Ganio; Alessandra Gazzola; Maria Filippa Addis; et al. (Antibiotics)
Background/Objectives: In the Aosta Valley, the alpine grazing system integrates livestock production and land management. Valdostana breeding has adapted to this mountainous region, but the spread of Staphylococcus aureus within pastures may impact animal health. The aim of this study was to provide an overview of S. aureus genotypes associated with antimicrobial resistance (AMR) and virulence profiles in four dairy herds in the Aosta Valley from July 2022 to August 2023. Methods: A total of 468 composite milk samples were collected at three timepoints: T1 (pasture-livestock system), T2 (farm-livestock system), and T3 (pasture-livestock system). S. aureus isolates were characterized by antimicrobial susceptibility testing, ribosomal spacer (RS)-PCR, multilocus sequence typing (MLST), PCR analysis for 28 virulence genes and 6 AMR genes, and adlb-targeted real-time PCR. Results: RS-PCR analysis of 82 S. aureus strains revealed 12 genotypes (GT) in eight clusters (CL). The most prevalent variant was GTRI (61%), followed by GTB (15%). Resistance to penicillin was high (69%), with CLR strains showing 88% resistance, and 51% resistance to amoxicillin plus clavulanate. All strains were susceptible to cephalosporins and oxacillin. Macrolide resistance was low (4%), and multi-drug resistance was 6%. AMR gene presence corresponded with susceptibility, with blaZ detected in 94% of CLR strains. CLR strains also possessed genes for biofilm formation and virulence factors. Conclusions: This study highlights the presence of AMR and virulence factors in S. aureus strains from alpine grazing systems, underscoring the need for ongoing monitoring to mitigate risks to animal health.